The Arctic council as an international organization of a new type - L. S. Voronkov; A. A. Smirnova (Международная аналитика)
The article emphasizes that the Arctic Council (AC) is a high level forum of cooperation, based on taking decisions by consensus that are carried out by member states on a voluntary basis and in accordance with their national interests. The AC does not meet the criteria of a classical international intergovernmental organization – IGO and may not be referred to as an international non-governmental organization – INGO due to its members. The high performance of the AC activity in the absence of a complex organizational structure, any executive body and a court is rooted in respect for national sovereignty of its member states. This informal international organization of new type became the core, around which a significant group of states, IGOs and INGOs, that received observer status at the AC, is created. Within the framework of its activity innovative tools of financing of ongoing programs have been developed. Participation of other member states of the AC in the anti-Russian sanctions does not become an obstacle for continuation of the close cooperation of all Arctic states in addressing the major problems of common concern in the Arctic. During the sanctions they established the Arctic economic council, signed the agreements on cooperation between coastal guards of all Arctic states, on scientific cooperation in the Arctic and on preventing unregulated fishing in the central part of the Arctic ocean. Negotiations on possible new agreements are going on between them. The model of informal international cooperation, demonstrated by the Arctic Council, is being successfully implemented also in the activities of the Nordic Council of Ministers, the Council of Barents/Euro-arctic Region, BRICS and other international organizations. This gave the authors the reason to conclude that this type of international organizations will be further developed in contemporary international relations.